Biología e importancia de las avispa del género Brachymeria Westwood, 1829 (Hymenoptera: Chalcididae) en el control biológico natural de insectos plagas - Mendieta Márquez, Dayanna Ivani (2023)
Insects of the order Hymenoptera are among the four most diverse in the world and play a fundamental role in virtually all terrestrial ecosystems. The parasitoid wasps of the Chalcididae family are considered primary parasitoid wasps of the orders Lepidoptera, Diptera, Coleoptera and Hymenoptera. The present investigative work proposes to review the importance of effective natural biological control by parasitoid wasps of the genus Brachymeri Westwood a . The parasitoid wasp of the genus Brachymeria is widely distributed and is considered the wasp of the most common genus of chalcidid parasites of a large number of pests of agricultural importance worldwide, as well as in Ecuador. The larval and pupal stages of the order lepidoptera were the most common hosts reported. The Brachymeria species present in Ecuador are B. subrugosa, B. costalimai, B. mnestor, B. subconica, B. incerta and B. cabira. The Brachymeria parasitoid wasps being reported as controllers of insect pests, locality and host surveys should be carried out, mainly Ecuadorian species to carry out detailed studies of biology as a tool that serve as recommendations for natural augmentative and inoculative biological control in crops from Ecuador.